TYPES OF TABOO EXPRESSIONS AND TRANSLATION STRATEGIES IN THE PROJECT X MOVIE - Sudiarta, I Komang Ngurah; Sulatra, I Komang; Utami, Ni Putu Verayanti (Program Studi Sastra Inggris, Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2023)
The aims of this research are to analyze the taboo words in the subtitle of Project X movie. According to Wardhaugh (2010:239), Taboo is the restriction or avoidance of action in any community that is thought to be harmful to its members, generating them worry, embarrassment, or shame. The use of taboo words can be found in our conversation on a daily basis and also in the entertainment, for instance in a movie. This study aims at (1) find out the taboo expression in the Project X movie, (2) categorizing and analyzing translation strategies used by the translator in translating taboo expressions found in the subtitle of the Project X movie, This study is a descriptive qualitative study. The data comes from the film Project X. The data comes from the movie's subtitles, which contain prohibited terms. This study uses Batistella's (2005) theory to define the different sorts of taboo words, as well as Baker's (1992) theory to examine the translation strategy. According to the findings, there are four categories of taboo expressions among the eighty data points examined. They are epithet (twenty five data), profanity (eight data) Vulgarity (thirty seven data), and obscenity (ten data). For the translation strategies are used translating taboo expressions, the results show that there are eight types of translation strategies. They are translation by more general word (nineteen data), translation by more neutral word/less expressive word (eight data), translation by cultural substitution (thirteen data), translation using loan word or loan word plus explanation (five data), translation by paraphrase using a related word (twelve data), translation paraphrase using unrelated word (two data), translation by omission (nineteen data), and translation by illustration (two data). Keywords: Taboo Expressions, Translation Strategy, Movie